方法および医学的利用 (2020)
本明細書に記載の発明は、それを必要とする対象においてエストロゲン受容体陽性乳癌を処置するための方法であって、前記対象に、治療有効量のＭＰＳ１阻害剤を投与することを含み、（ｉ）前記対象が、内分泌療法で以前に処置されている；および／または（ｉｉ）前記乳癌が、内分泌療法に対して抵抗性がある方法を提供する。 The invention described herein provides a method for the treatment of an oestrogen receptor positive breast cancer in a subject in need thereof comprising administering to said subject a therapeutically effective amount of an MPS1 inhibitor, wherein: (i) said subject has previously been treated with an endocrine therapy; and/or (ii) said breast cancer is resistant to endocrine therapy.